Analogy motor learning by young children: a study of rope skipping. Issue 2 (7th February 2017) - Tse, Andy C. Y.; Fong, Shirley S. M.; Wong, Thomson W. L.; Masters, Rich
Abstract: Research in psychology suggests that provision of an instruction by analogy can enhance acquisition and understanding of knowledge. Limited research has been conducted to test this proposition in motor learning by children. The purpose of the present study was to examine the feasibility of analogy instructions in motor skill acquisition by children. Thirty-two children were randomly assigned to one of the two instruction protocols: analogy and explicit instruction protocols for a two-week rope skipping training. Each participant completed a pretest (Lesson 1), three practice sessions (Lesson 2–4), a posttest and a secondary task test (Lesson 5). Children in the analogy protocol displayed better rope skip performance than those in the explicit instruction protocol ( p  < .001). Moreover, a cognitive secondary task test indicated that children in the analogy protocol performed more effectively, whereas children in the explicit protocol displayed decrements in performance. Analogy learning may aid children to acquire complex motor skills, and have potential benefits related to reduced cognitive processing requirements.